Neurodevelopmental Disorders and Connective Tissue-Related Symptoms: An Exploratory Case-Control Study in Children - Leonardo Zoccante; Gianfranco Di Gennaro; Erika Rigotti; Marco Luigi Ciceri; Andrea Sbarbati; Marco Zaffanello (Children)
Background/Objectives: Autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), and Tourette syndrome (TS) are neurodevelopmental disorders (NDDs) with overlapping symptoms, suggesting a partially shared genetic origin. This study investigates the prevalence of connective tissue-related conditions in individuals with ASD, ADHD, or TS. Methods: A questionnaire was administered to families of 120 individuals with ASD, ADHD, or TS, collecting sociodemographic data and examining 10 types of disorders affecting various organs and systems. Statistical analyses were performed using STATA 16.0, with the significance level set at 5%. Results: Among the 120 patients, 48 had ASD, 36 had ADHD, and 36 had TS. Flat feet were significantly more common in individuals with ASD (52.1%; OR 7.20; p < 0.001), ADHD (52.8%; OR 6.73; p = 0.001), and TS (38.9%; OR 3.70; p = 0.034) compared to controls (13.6%). Hypersensitivity was more frequent in individuals with ASD (56.3%; OR 5.90; p = 0.001), ADHD (50.0%; OR 4.11; p = 0.011), and TS (58.3%; OR 5.35; p = 0.003) compared to controls (18.2%). Myopia and ptosis were more common in ADHD (30.6%). There was a possible trend towards orthodontic device use in TS (OR 3.20; p = 0.076). Flat feet and hypersensitivity were also common in fathers (31.0% and 36.4%, respectively), mothers (31.0% and 15.2%), and patients (43.8% and 55%). Conclusions: The findings of this study highlight the significant associations between ASD, ADHD, and TS and specific physical symptoms, such as flat feet, sensory hypersensitivity, and other connective tissue-related manifestations. The familial prevalence of these symptoms suggests a potential genetic underpinning, further supporting the hypothesis of shared aetiological pathways. These insights underscore the need for interdisciplinary research to explore the mechanisms linking neurodevelopmental and connective tissue disorders, aiming to improve diagnosis and management strategies.